Geomicrobiology of a weathering crust from an impact crater and a hypothesis for its formation - Cockell,CS; Kennerley,N; Lindstrom,M; Watson,JS; Ragnarsdottir,V; Sturkell,E; Ott,S; Tindle,AG (Geomicrobiology Journal: an international journal of geomicrobiology and microbial biogeochemistry, 2007)
Understanding the role of microbe-mineral interactions in rock weathering is vital to an understanding of nutrient availability to the biosphere and, in so far as weathering influences carbon dioxide drawdown, climate control. We studied a weathering crust on a resurge tsunami deposit (Loftarstone) from the 455 Ma old Lockne impact crater, central Sweden with an integrated approach using XRD, electron microprobe analysis, SEM-EDS and GCMS analysis of organics. The lichens and fungal hyphae network preferentially weather the chlorite in the Loftarstone compared to feldspars and quartz. We demonstrate, using a fungal isolate (identified by ITS sequencing), that biologically induced dissolution of the calcite component produces cavities which increase the surface area of interaction between the biota and the rock substrate. The weathering crust exfoliates from the rock surface in sheets, which we attribute to the dissolution of the calcite matrix. We present a hypothesis for the crust development. As well as providing insights into weathering on substrates derived from a diversity of high-energy geological disturbances, such as impact events and tsunamis, the weathering crust provides a model system to understand weathering processes in other common lithologies with mixed mineralogies at small spatial scales, including many sedimentary rocks. This work reveals how each different clast plays a unique part in the weathering process, leading to a well-defined weathering sequence.